A review on cost-effectiveness and cost-utility of psychosocial care in cancer patients - Femke Jansen; Valesca van Zwieten; Veerle M. H. Coupe; C Rene Leemans; Irma M Verdonck-de Leeuw (Asia-Pacific Journal of Oncology Nursing, 2016)
Several psychosocial care interventions have been found effective in improving psychosocial outcomes in cancer patients. At present, there is increasingly being asked for information on the value for money of this type of intervention. This review therefore evaluates current evidence from studies investigating cost-effectiveness or cost-utility of psychosocial care in cancer patients. A systematic search was conducted in PubMed and Web of Science yielding 539 unique records, of which 11 studies were included in the study. Studies were mainly performed in breast cancer populations or mixed cancer populations. Studied interventions included collaborative care (four studies), group interventions (four studies), individual psychological support (two studies), and individual psycho-education (one study). Seven studies assessed the cost-utility of psychosocial care (based on quality-adjusted-life-years) while three studies investigated its cost-effectiveness (based on profile of mood states [mood], Revised Impact of Events Scale [distress], 12-Item Health Survey [mental health], or Fear of Progression Questionnaire [fear of cancer progression]). One study did both. Costs included were intervention costs (three studies), intervention and direct medical costs (five studies), or intervention, direct medical, and direct nonmedical costs (three studies). In general, results indicated that psychosocial care is likely to be cost-effective at different, potentially acceptable, willingness-to-pay thresholds. Further research should be performed to provide more clear information as to which psychosocial care interventions are most cost-effective and for whom. In addition, more research should be performed encompassing potential important cost drivers from a societal perspective, such as productivity losses or informal care costs, in the analyses.